Livestock and climate change: the key actors and the sufferers of global warming - SINGH, VIR; RASTOGI, AKANKSHA; NAUTIYAL, NANDA; NEGI, VRINDA (The Indian Journal of Animal Sciences, 2017)
There are many agents of climate change. Livestock are one of them. Livestock contibutes to climate change by adding to greenhouse gases (GHGs). At the same time, livestock are one of the worst sufferers of the climate change. This paper discusses how the GHG emissions from livestock sector are phenomenol for climate change and how the climate change is affecting the performance of this sector and what could be the potential impact of this sector on public health. Livestock are more sensitive to climate change than cropping systems. Crossbred cattle are still more sensitive than their indigenous counterparts. There are strategies of reducing impact of climate change on livestock and improve their overall performance. Improved and effective management of natural resources and livestock sector would be phenomenal for reducing methane emission by changing the physiological processes inside rumen. There is need to formulate a policy to replace livestock products with better and more nutritive alternatives of which there is enormous scope in this world. Imposition of carbon taxes on meat industry would also help reduce carbon emissions from livestock sector.